(M)Unc13s in Active Zone Diversity: A Drosophila Perspective - Piao, Chengji; Sigrist, Stephan J. (Frontiers in Synaptic Neuroscience, 2022)
The so-called active zones at pre-synaptic terminals are the ultimate filtering devices, which couple between action potential frequency and shape, and the information transferred to the post-synaptic neurons, finally tuning behaviors. Within active zones, the release of the synaptic vesicle operates from specialized “release sites.” The (M)Unc13 class of proteins is meant to define release sites topologically and biochemically, and diversity between Unc13-type release factor isoforms is suspected to steer diversity at active zones. The two major Unc13-type isoforms, namely, Unc13A and Unc13B, have recently been described from the molecular to the behavioral level, exploiting Drosophila being uniquely suited to causally link between these levels. The exact nanoscale distribution of voltage-gated Ca2+ channels relative to release sites (“coupling”) at pre-synaptic active zones fundamentally steers the release of the synaptic vesicle. Unc13A and B were found to be either tightly or loosely coupled across Drosophila synapses. In this review, we reported recent findings on diverse aspects of Drosophila Unc13A and B, importantly, their nano-topological distribution at active zones and their roles in release site generation, active zone assembly, and pre-synaptic homeostatic plasticity. We compared their stoichiometric composition at different synapse types, reviewing the correlation between nanoscale distribution of these two isoforms and release physiology and, finally, discuss how isoform-specific release components might drive the functional heterogeneity of synapses and encode discrete behavior.